Left atrial anomalous muscular band as incidental finding during video-assisted mitral surgery - Saade, Wael; Baldascino, Francesco; De Bellis, Antonio; D’Abramo, Mizar; Iaccarino, Alessandra; Frati, Giacomo; Greco, Ernesto (Journal of Thoracic Disease, 2018)
Congenital fibromuscular bands have been described in left ventricle or right atrium and have been diagnosed by echocardiography and CT scan. The first report of anomalous band in the left atrium was described in 1897 by Rollestone (1). We hereby present a case of a patient with an incidental finding of left atrial band during a minimally invasive mitral surgery procedure.